2006
DOI: 10.1097/01.pec.0000195760.97199.7e
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Web-Based Education Program on Reducing Medication Dosing Error

Abstract: The Web-based education program on the proper use of the Broselow Pediatric Resuscitation Tape could improve dosing accuracy and reduce dosing time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 14 publications
0
45
0
Order By: Relevance
“…Two studies used an acted-out clinical scenario to assess participants' assimilation of material taught. 12,18 Both were positive. One study used reported practice change and assessed attitude and confidence via questionnaire 13 and did not show a significant effect.…”
Section: Outcome Evaluationmentioning
confidence: 95%
“…Two studies used an acted-out clinical scenario to assess participants' assimilation of material taught. 12,18 Both were positive. One study used reported practice change and assessed attitude and confidence via questionnaire 13 and did not show a significant effect.…”
Section: Outcome Evaluationmentioning
confidence: 95%
“…Quality of prescribing has also been implicated, with 10-fold errors most commonly attributed to misplaced decimals, the use of tailing zeros and illegible prescriptions 4. Several strategies and solutions have been employed to minimise the incidence of dose errors, including calculators,5 educational programmes,6 7 computer software8 9 and colour-coded tapes 10. A recent systematic literature review commissioned by the Patient Safety Research Programme in England has found that of the interventions that have been used to reduce dose errors, computerised physician order entry (CPOE) or electronic prescribing (EP) is the commonest and shows most promise 11.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies to reduce PEs and AEs in hospitalized children have investigated the impact of a single intervention such as education or training . The results of those studies showed that none of the interventions were superior in terms of error reduction.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Many studies to reduce PEs and AEs in hospitalized children have investigated the impact of a single intervention such as education or training. [18][19][20][21][22][23][24][25][26][27][28][29][30] The results of those studies showed that none of the interventions were superior in terms of error reduction. The processes of prescribing and administration are complex because the causes of errors are multifactorial 8 and different conditions for behaviours are involved.…”
Section: What Is Known and Objectivementioning
confidence: 99%